Pertanggungjawaban Hukum Terhadap Praktik Makelar Kasus Oleh Zarof Ricar Di Pengadilan - Andryawan, Andryawan; Tsabita, Nabilla Mahva; Sanyoto, Alicia Andromeda; Purba, Jeremy Exaudi (Peneliti.net, 2025)
In the legal context, case brokering can be classified as a corruption offense because it refers to individuals who influence court decisions to win certain cases through unlawful means, such as bribery. In practice, case brokering involves intervening in the law enforcement process, from investigation to court decisions. The purpose of this study is to analyze the legal provisions regarding the practice of case brokering in court and the legal liability that can be imposed on Zarof Ricar for alleged case brokering practices. In this research we used the normative research method which focuses on the applicable legal rules related to the provisions and legal liability for the practice of case brokering in court. Through this research, it is concluded that Zarof's actions have violated the ASN code of ethics in accordance with applicable legal regulations and because his actions have undermined the principle of judicial independence, Zarof can be sanctioned for his actions. In addition, Zarof may also be subject to sanctions in the form of confiscation of assets obtained from corruption. Thus, to avoid such actions in the future, the Attorney General's Office and the Supreme Court must thoroughly investigate the practice of case brokering by Zarof Ricar and impose strict sanctions on the individuals involved.